Macrophage Polarization in Leishmaniasis: Broadening Horizons - Tomiotto-Pellissier, Fernanda; Bortoleti, Bruna Taciane da Silva; Assolini, João Paulo; Gonçalves, Manoela Daiele; Carloto, Amanda Cristina Machado; Miranda-Sapla, Milena Menegazzo; Conchon-Costa, Ivete; Bordignon, Juliano; Pavanelli, Wander Rogério (Frontiers in Immunology, 2018)
Leishmaniasis is a vector-borne neglected tropical disease that affects more than 700,000 people annually. Leishmania parasites cause the disease, and different species trigger a distinct immune response and clinical manifestations. Macrophages are the final host cells for the proliferation of Leishmania parasites, and these cells are the key to a controlled or exacerbated response that culminates in clinical manifestations. M1 and M2 are the two main macrophage phenotypes. M1 is a pro-inflammatory subtype with microbicidal properties, and M2, or alternatively activated, is an anti-inflammatory/regulatory subtype that is related to inflammation resolution and tissue repair. The present review elucidates the roles of M1 and M2 polarization in leishmaniasis and highlights the role of the salivary components of the vector and the action of the parasite in the macrophage plasticity.